Association Between Mental Health Literacy and Stigma: A Review - Lamichhane, Bishnu-Barsha (AMC Journal, 2023)
People with mental illness often do not receive proper mental health services. Lack of knowledge and social stigma are factors contributing to the low prevalence of seeking help for mental health problems. In low- and middle-income countries, only around one-fifth of the population receives adequate treatment, and this situation is similar in South Asian countries. Objective: The main objective of this review is to identify research on mental health literacy and stigma in SAARC countries. Methods: Three databases (PubMed, SCOPUS, and EMBASE) were searched up to September 20, 2022. A total of 47 articles were included in the review, of which five met the inclusion criteria. Thematic analysis was conducted to review the articles. Results: The relationship between mental health literacy and stigma was found to be negative, meaning that an increase in literacy decreased stigma and vice versa. The main barriers to treatment were stigma and lack of financial means to afford care. Conclusion: Government planners and policymakers should implement mental health literacy programs to reduce stigma and encourage help-seeking behavior among individuals with mental illness. The data highlights the positive effects of anti-stigma campaigns on mental health literacy and help-seeking.